Competence Development and Management in Malaysian Railway Traffic Management System - Sundaram Ts, Shanmuga; Shavarebi, Dr. Kamran (Asian Journal of Interdisciplinary Research, 2020)
The purpose of this paper is to introduce a systematic approach to develop and manage competence of employee in the field of Traffic Management System (TMS) of Malaysian railway industry. The outcome of this research shall conclude a framework for competence management and define a benchmark for practice in this industry. Previous studies in competence management in the field of TMS mainly limited to non-Malaysian railway and from different type of railway network. The framework for this research study uses component of competence as core element mediate by suitable element to develop and enhance competence. This descriptive quantitative research study uses suitable competency model to explore the competence of the TMS employee. Following this, a suitable technique and method for learning and training method propose for Malaysian railway TMS operation employee. This whole process is summarized into a competence management framework.